2017
DOI: 10.1186/s12884-016-1214-3
|View full text |Cite
|
Sign up to set email alerts
|

Do experiences with pregnancy, birth and postnatal care in Norway vary by the women’s geographic origin? a comparison of cross-sectional survey results

Abstract: BackgroundA national survey was conducted to measure and benchmark women’s experiences with pregnancy, birth and postnatal care in Norway. The purpose of this secondary analysis is to explore potential variation in these experiences with regard to the survey respondents’ geographic origin.MethodsData were collected in a national observational cross-sectional study, by a self-administered questionnaire and from registries. The questionnaire collects patient reported experience measures (PREMS) of mainly nontech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…We found no association between overall satisfaction and mother's region of birth in our study, in agreement with other studies, 19 48 49 including one conducted in Norway. 50 While some studies have found higher satisfaction among migrants compared with non-migrants, 35 41 42 other studies have found the opposite. 40 However, we did not include non-migrants, as our aim was not to compare migrant women to the majority population.…”
Section: Open Accessmentioning
confidence: 99%
“…We found no association between overall satisfaction and mother's region of birth in our study, in agreement with other studies, 19 48 49 including one conducted in Norway. 50 While some studies have found higher satisfaction among migrants compared with non-migrants, 35 41 42 other studies have found the opposite. 40 However, we did not include non-migrants, as our aim was not to compare migrant women to the majority population.…”
Section: Open Accessmentioning
confidence: 99%
“…These results are comparable with findings from other studies showing overall high levels of satisfaction with maternal care in Norway. 7,10 The observed scores for the scales User Participation, Accessibility, Information, and Midwife were generally high, with the highest result for the Midwife scale. The overall high levels of satisfaction with midwives at public health clinics were also frequently expressed in the user comments, which highlighted midwives' high levels of relational and professional competence, as well as their good accessibility.…”
Section: Discussionmentioning
confidence: 96%
“…Sjetne and Iversen 10 found no systematic differences in experiences of maternal care in Norway based on geographical origin. However, it is important to note that their study assessed satisfaction shortly after birth, which may lead to an overestimation.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations